2015
DOI: 10.1016/j.indcrop.2015.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Use of wheat bran arabinoxylans in chitosan-based films: Effect on physicochemical properties

Abstract: a b s t r a c tThe aim of this work was to evaluate physicochemical properties of chitosan-based films with different fractions of arabinoxylans (AXs). Five fractions composed by AXs or mixtures of AXs and arabino-xylooligosaccharides (AXOS) obtained through three different processes were added to chitosan-based films. These films were obtained by solvent casting and characterized in terms of water vapor permeability (WVP), opacity, thickness, moisture content and mechanical properties (i.e., tensile strength … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 31 publications
(46 reference statements)
4
42
2
Order By: Relevance
“…The chitosan film was the most transparent compared to the BGP film. Our results are in good agreement with the results of Costa et al (2015), who found that the opacity of plain chitosan film is lower than the opacity of wheat bran arabinoxylans-chitosan composite films. The 50BGP:50Ch film decreased the opacity from 24.82 to 14.53 % compared to the BGP film.…”
Section: Optical Properties Of the Bgp Composite Filmssupporting
confidence: 92%
“…The chitosan film was the most transparent compared to the BGP film. Our results are in good agreement with the results of Costa et al (2015), who found that the opacity of plain chitosan film is lower than the opacity of wheat bran arabinoxylans-chitosan composite films. The 50BGP:50Ch film decreased the opacity from 24.82 to 14.53 % compared to the BGP film.…”
Section: Optical Properties Of the Bgp Composite Filmssupporting
confidence: 92%
“…It was observed that the films produced in this work were more opaque than the films of gelatin and PVA (Y < 3.1; x < 0.1 mm), or more opaque than the films of pigskin gelatin (Y < 0.5; x < 0.1 mm), which were extremely transparent, or more opaque than arabinoxylans and arabino‐xylooligosaccharides (Y < 16.49) . This high opacity of films with chitosan can prevent the occurrence of damages caused by excessive incidence of light in the food product, but can affect the consumer acceptance because they do not clearly see the product.…”
Section: Resultsmentioning
confidence: 66%
“…70 From a technological point of view, AXs have shown great potential as biomaterials due to their biocompatibility, biodegradability, and barrier properties to oxygen. 71,72 The extracted polymeric F-AX fractions show excellent potential for the design of bio-based materials, combining the good rheological and viscoelastic properties of the polysaccharide core with the inherent antioxidant properties of the phenolic moieties. Moreover, the FA could offer further interesting functionalities, such as UV absorbance 73 and the possibility for enzymatic crosslinking.…”
Section: Antioxidant Activities Of the Ax Fractionsmentioning
confidence: 99%